Kentropyx viridistriga, Green Kentropyx - Pelegrin, Nicolas (2019)
Kentropyx viridistriga has been assessed as Least Concern as the species has a wide range acrossParaguay, and areas of Argentina, Brazil, and Bolivia, with no known widespread threats. This species is known from Paraguay, northern Argentina, Brazil (in the state of Mato Grosso), and Bolivia (Beni, Santa Cruz and Cochabamba). This species is found in Cerrado, Chaco and Pantanal biomes. It also inhabits open areas within rainforest, often in moist conditions, occupying river beaches and flood plains. The species has been found on floating vegetation. This species is considered to be threatened in Argentina by habitat loss; but on a range-wide scale no major threats are known.